GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 388926135 species occurrences available in GBIF matching the query: DatasetKey: not (EOD - eBird Observation Dataset). The dataset includes 388926135 records from 13192 constituent datasets: 53985 records from BioMar - LIFE project. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 197872 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 3633 records from Bioimages. 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 113 records from Naturalis Biodiversity Center (NL) - Crustacea. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 5549 records from Diplopoda (NSMK-DI). 97 records from DMNH Eggs. 375 records from Phthiraptera. 77 records from Empria and Monsoma in Japan. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 1 records from Arthropoden aus südostalpinen Höhlen.. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 139 records from The Bat Conservation Trust - Woodland Survey. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 151010 records from Marie-Victorin Herbarium (MT). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 66 records from Wedeler Au. 9703 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 6 records from Hemichordata collection of National Museum of Nature and Science. 398 records from Tsetse flies of East Africa update. 58475 records from Oregon State University Herpetological Collection. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 6543 records from University of Ghent - Zoology Museum - Vertebratacollectie. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 457 records from Microbial Observatory of the Laboratoire Arago. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 161085 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 373 records from Otter survey of Ireland 2004 & 2005. 396 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 3107 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 140 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 5 records from Arthropoden aus südostalpinen Höhlen.. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 311768 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10072 records from Guadeloupe_Herbier. 28385 records from Plan de vertebrados de la Patagonia. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 1 records from Nothrus spinifer. 45 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 2312 records from Mycological collection of the National Museum. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 31 records from Siphonaptera. 8220342 records from OEH Atlas of NSW Wildlife. 4438 records from ISE - Herbário ISE. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 99300 records from Landesmuseum Kärnten. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 1 records from Celaeno plicata. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 11789 records from JOI - Herbário Joinvillea. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 3509 records from Entocytheridae (Ostracoda) World Database. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 1 records from Nothrus runcinatus. 1702 records from BioGIS - Bryophytes - HUJ collections. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 78 records from Guyane_française_caféier. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 191 records from Herpetofauna laguna El Tinije. 1238 records from Insect Collection (CeStuBio). 1 records from Hoplophora globosa. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 33 records from Revision von Suctobelba trigona (Michael, 1888). 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 3 records from MSB Mammal Observations (Arctos). 90189 records from African Rodentia. 106428 records from Jordal. 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 68221 records from University of Vienna, Institute for Botany - Herbarium WU. 9302 records from Ants from the Paraguayan dry Chaco. 379 records from WNMU Fish Collection (Arctos). 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 20870 records from HUEM - Herbário da Universidade Estadual de Maringá. 7735 records from CSUC Vertebrate Collection. 66081 records from HUFU - Herbarium Uberlandense. 20 records from Heteroptera - SMNG. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 2922 records from National Lesser Horseshoe Bat Database. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 267464 records from MVZ Herp Collection (Arctos). 62283 records from PRECIS (KwaZulu-Natal Herbarium). 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty and Biswas. 10633 records from Biological Records Centre - Collembola Recording Scheme. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 27975 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 3204 records from Faunal Inventory of Morysin Nature Reserve. 129 records from Mammalia (KNAM-MM). 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 661414 records from Phanerogamic Botanical Collections (S). 20043 records from Mollusca collection of National Museum of Nature and Science. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1 records from Damaeus concolor. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 5709 records from Coleoptera of Piska Forest. 712 records from Herbier G. Garapin (BOUM). 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 1998 records from Aves de la cuenca media del río Bogotá. 89874 records from ecoscope_observation_database. 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 15387 records from UFG - Herbário da Universidade Federal de Goiás. 5181 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 326 records from Colección nacional de palmas de Colombia - JBQ. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 2546 records from The atlas of butterflies in Kraków. 231131 records from MVZ Mammal Collection (Arctos). 8136 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 128959 records from Australian National Wildlife Collection provider for OZCAM. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 1 records from Zetes longiusculus. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 288 records from Fungi of Słowiński National Park, Poland. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 10358 records from Census of the flora of Benin. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 12065 records from Tromsø Museum, Bryophytes. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 34 records from New records in vascular plants alien to Kyrgyzstan. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 60672 records from QLD DERM Coastal Bird Atlas (Trial). 7427 records from Weevils of the Tatra Mts.. 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 4579 records from Herbarium WRSL, Flora of the Silesia. 1336963 records from AntWeb. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 159 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 38689 records from Marine species distributions in Irish coastal waters. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 1025 records from Irish Marine Turtle Database. 30872 records from Online Atlas of vascular plants 2012-2020. 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 3335170 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 4354 records from Portuguese Seaweeds. 60573 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 356 records from Morphologische Daten von Puffinus creatopus. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 511 records from Coleoptera of Swierklaniec Forest. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1 records from Oribates calcaratus. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 4 records from Fossil (SMNH-FO). 3082 records from dec2011. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 10102 records from Herbarium Vonderau - FULD. 35287 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 270 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 99 records from French national collection of Solanum tuberosum. 408 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 2376 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 1020718 records from Consortium of California Herbaria. 13597 records from Orthopteroidea. 6179 records from Southern Cape herbarium. 15637 records from CCBER Herpetology Collection. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 51527 records from IAC - Herbário do Instituto Agronômico de Campinas. 9788 records from SANT-Lich. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 561820 records from Bee Biology and Systematics Laboratory. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 8 records from Order Diptera, family Mydidae. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 88901 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 1 records from Hoplophora laevigata. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 1284 records from Collection of Heteroptera. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 2007 records from Palaeobiology collection, FAU Erlangen. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 52666 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 834 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5733 records from Small Mammal Research Database. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 1 records from Red list project inventory, bryophytes. 51 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 16 records from Tettigettalna josei (Boulard, 1982) (Hemiptera: Cicadoidea): first record in Spain, with notes on the distribution, genetic variation and behaviour of the species. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 2116 records from Collection entomologique Pierre Lachiver. 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 46954 records from SPSF - Herbário Dom Bento José Pickel. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Nothrus segnis. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 28626 records from SANT-Algae. 1124142 records from PRECIS. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 1 records from Celaeno obsoleta. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 1 records from Oribates gilvipes. 389 records from Amphibian and Reptilian (KIEE-AR). 6541 records from Likona Invertebrates. 3182 records from Finnish Entomological Database: Heteroptera. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 4686 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 177466 records from CAS Entomology (ENT). 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 485 records from National Taiwan Ocean University. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 59534 records from Zoology (Museum of Evolution - Uppsala). 1 records from Hoplophora ferruginea. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6237 records from Plecoptera. 253095 records from Lyman Entomological Museum (LEMQ). 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 1 records from Oribates fuscipes. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 1196 records from Entomological collection of the National Museum. 1 records from Zetes cespitum. 26880 records from KUBI Ornithology Tissue Collection. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2494 records from Marine Environmental Monitoring - Marine Turtles. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 33070 records from CSIRO Ichthyology provider for OZCAM. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 1387717 records from Fishbase. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 13909 records from Albany Museum. 190 records from Relative abundance of ostracods in sediment core Sv09. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 7693 records from NHM, Heteroptera. 4461 records from Paläontologie Marburg. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 4544 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 1 records from Pelops torulosus. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 121542 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 29587 records from EPA River Biologists data. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 6 records from Collection Myriapoda - SNSD. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 5053399 records from Southern African Bird Atlas Project. 1 records from Nothrus mutilus. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 75791 records from SAIAB. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 16 records from Taxonomic review of the genus Wasmannia.. 165769 records from KUBI Mammalogy Collection. 4447 records from Lepidoptera (Observations). 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 43480 records from UFP - Herbário UFP - Geraldo Mariz. 3 records from First report of the genus Conostigmus Dahlbom (Hymenoptera: Ceraphronoidea: Megaspilidae) from India with description of a new species. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 3797 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 17618 records from BioGIS - Mammals - INPA database. 461 records from Guadeloupe_Bananier. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 18896 records from SPF - Herbário da Universidade de São Paulo. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 27639 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 66722 records from SANT herbarium vascular plants collection. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 177 records from BIRDRACE Die Kielbris. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 2513 records from Carabidae of the Tatra Mts.. 9349 records from Harriet Irving Botanical Gardens (HIBG). 1 records from Miriapodi di alcune grotte della Campania. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 372 records from Colección de Entomología - Arthropoda. 444 records from Insect Collection from New Caledonia. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 99463 records from NPL collections. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 15 records from Projeto Abrace o Boto Cinza. 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 7509 records from Perot Museum of Nature and Science. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 61 records from Registros restauración ecológica- Magdalena medio. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 195719 records from Colección Herbario Federico Medem Bogotá - FMB. 2 records from First record of Orobdella kawakatsuorum (Hirudinida: Arhynchobdellida: Erpobdelliformes) from Kunashir Island, Kuril Islands. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 5730 records from Cercle des mycologues de Montréal Fungarium (CMMF). 409 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 1854895 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 2174 records from MLZ Mammal Collection (Arctos). 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 1 records from On centipedes (Chilopoda) of Albania, 2. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 1573019 records from SA Flora (BDBSA). 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 88018 records from NINA Vanndata øvrige arter. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 355 records from Culture Collection of Cryophilic Algae. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 756 records from Targeting a portion of central European spider diversity for permanent preservation. 3688 records from Clare Biological Records Centre dataset. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 599260 records from FLORIVON. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 198502 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 96 records from Trichoptera (caddisflies) of Ireland. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 70738 records from University of Alberta Vascular Plant Herbarium (ALTA). 3 records from Note su alcune specie di chilopodi della regione palestinese. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 3 records from New data of three rare belondirid species (Nematoda, Dorylaimida, Belondiridae) from Vietnam, with the first record and description of the male of Oxybelondira paraperplexa Ahmad & Jairajpuri, 1979. 1 records from Eremaeus hepaticus. 13993 records from Herpetology. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 17802 records from The Bat Conservation Trust - Colony Count Survey. 1 records from Arthropoden aus südostalpinen Höhlen.. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 13086 records from Collection of Coleoptera. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 24657 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 47499 records from Sphaeroceridae Collection. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 7671 records from HERBAM - Herbário da Amazônia Meridional. 19127 records from Biological Records Centre - Cerambycidae Dataset. 68304 records from IICT Herbário LISC. 157869 records from Lund Museum of Zoology - Insect collections (MZLU). 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 634257 records from Inventario Español de Especies Terrestres (MAGRAMA). 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 370 records from Collection Crustacea - KAUMM. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 2082 records from Vietnam Type Culture Collection. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 38200 records from Herbario Universidad de Antioquia (HUA). 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 88263 records from URM - Herbário Pe. Camille Torrand. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 1 records from Hoplophora decumana. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 50 records from Description of Notarius biffi n. sp. and redescription of N. insculptus (Jordan and Gilbert) (Siluriformes: Ariidae) from the eastern Pacific, with evidence of monophyly and limits of Notarius.. 44 records from Solanum_baretiae. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 1 records from Oribates flammula. 3257 records from fundiv france database. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 7458 records from Colección de Reptiles del Instituto Alexander von Humboldt. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 1562 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 6730 records from National Museum of Marine Biology and Aquarium. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 69982 records from Lepidoptera collection, Natural History Museum, University of Oslo. 3647557 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 24 records from Sphodromantis viridis (Forskal, 1775): New for Portugal and new records of the rare and small mantids Apteromantis aptera (Fuente, 1894) and Perlamantis allibertii Guérin-Méneville, 1843 in the country (Mantodea: Mantidae and Amorphoscelidae). 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 1 records from Cepheus latus. 45159 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 173415 records from Hymenoptera specimen database of Kyushu University. 1 records from Oribates picipes. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 585 records from Ascomycetes of Russian Fennoscandia. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 77 records from Xiphosura collection of National Museum of Nature and Science. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 1481 records from Reptilia notes, NTNU, Trondheim. 1 records from On the Chilopoda from Turkey. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 2 records from Kirchenforst. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 6855 records from Echinoderm collection of National Museum of Nature and Science. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 52 records from Isotope tracer experiment: meiofauna counts. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 63 records from (Data S1) Palynology of ODP Site 119-739. 24855 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 2576 records from Hosted Invertebrate Collection 01. 374 records from published_chenopodium_vulvaria_observations. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 119366 records from The digitization of plant specimens of NTU. 15934 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 365 records from Colección Herpetológica de la Patagonia. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 6997 records from CHAS Vertebrates. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 4857 records from University of Alberta Museums, Entomology Collection. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 5850 records from UAFMC Fish. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 74208 records from NCSM Fishes Collection. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 2848 records from Kangawalla Bird Sightings. 57879 records from Albany Museum Grant. 538 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 223433 records from Phytochorologie des départements français. 471 records from Aschelminth collection of National Museum of Nature and Science. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 3567 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 2880 records from Coleoptera, NEF. 11 records from Pollen profile from sediment core AV14_K2-4. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 213760 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 185 records from Klasse 3a. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 12512 records from ULg_Hexapoda. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 24694 records from Amphibian Specimens. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 752 records from The Fish Collection at the Zoologische Staatssammlung München. 1 records from Zetes rubens. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 9879 records from Bibliographic records of Angola mammals. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 3956 records from SMDB - Santa Maria Departamento de Biologia. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 535913 records from BioFokus. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 6 records from First description of the male caste of the Himalayan endemic ant Lasius alienoflavus Bingham, 1903 (Hymenoptera: Formicidae), with re-description of the female and queen castes . 767 records from BioGIS - Bats - Asaf Tsoar database. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 15630 records from Vertebrats d'Andorra. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 9248 records from UAM Fish Collection (Arctos). 32 records from Archaea Collection in BCRC. 42861 records from DMNS Bird Collection (Arctos). 81388 records from natagora-earlybirds. 2 records from Arthropoden aus südostalpinen Höhlen.. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 255 records from GENT Lactarius Deliciosi. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 712 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 12434 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 3945 records from TTRS Ornithology. 582 records from Bioblitz 2013 Copenhagen Denmark. 65486 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1 records from Nothrus pollinosus. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 1364 records from Irish Collembola records. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 71463 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1 records from Myriopoden von Epirus. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 1 records from Études myrmécologiques en 1886.. 7410 records from Helgeland Museum, Lepidoptera. 5538 records from Colección Alberto Tinaut (Formicidae). 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 26624 records from Monitoring data from the federal state Bavaria (Germany). 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 397 records from Danish Lacewings (Neuroptera). 9997 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 51803 records from CESJ - Herbário Leopoldo Krieger. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 74752 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2599 records from Insecta ZMK. 102 records from Sipuncula collection of National Museum of Nature and Science. 2654 records from Collection of Hymenoptera. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5569 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 58 records from Mamíferos laguna El Tinije. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 11731 records from HAS-Algae - Coleção Ficológica do HAS. 32962 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 15879 records from HAMAB - Herbário Amapaense. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 90399 records from CUMV Fish Collection (Arctos). 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 1 records from Nothrus pigerrimus. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 27167 records from Bird tissue collection, Natural History Museum, University of Oslo. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 1 records from Zetes ephippiatus. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 241 records from BIRDRACE RennVögel Münsterland. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 155 records from Megophthalmidia_of_North_America. 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 1 records from Zetes fuscomaculatus. 21760 records from CUMV Mammal Collection (Arctos). 151 records from Molluscan fauna of Gueishan Island of Taiwan. 820552 records from Fauna Atlas N.T.. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 13717 records from OUPR - Herbário "Professor José Badini". 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 52 records from CIM Specimens. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 29263 records from Tromsø Museum, Fungi. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 13413 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 102 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 1323 records from Algae (KBRC-AG). 1 records from Nothrus canaliculatus. 4996 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 122409 records from UAM Mammal Collection (Arctos). 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 2475 records from HSU Wildlife Eggs and Nests. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 13325 records from Herbier du Bénin. 6 records from MfN - Micropaleontology. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 6065 records from LISU Herbario Angola. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 519292 records from Museum Victoria provider for OZCAM. 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 3768 records from Eggs Specimen. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 27079 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 11392 records from Danish Plant Bugs (Miridae). 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 1948 records from CCBER Mammalogy Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 136 records from Plants galls. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 40109307 records from Artdata. 464 records from Lepidoptera collection, NTNU, Trondheim. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 2577 records from Shellfish (WSHN-MS). 711 records from Odonata collection, NTNU, Trondheim. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 34609 records from Butterflies of Ireland. 62015 records from Atlas of Iberian water beetles (ESACIB database). 9123 records from Flora of Słowiński National Park, Poland. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 8579 records from The atlas of breeding birds in Małopolska. 71 records from (Data S1) Palynology of ODP Site 113-696. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 6 records from Arthropoden aus südostalpinen Höhlen. 1803 records from Flora of tanzania. 314 records from Peces laguna El Tinije. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 2412 records from Ohio University Invertebrate Paleontology Collection. 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 1476 records from Harvestmen_of_French_Guiana. 2815 records from Helgeland Museum, Araneae. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 3333 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 47601 records from CRCM Vertebrate Collection. 3 records from Diatom abundance of Hole 38-338, Part 2. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 18940 records from Cowan Tetrapod Collection - Mammals. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 1905 records from BioGIS - Reptiles - INPA database. 777 records from INRA-Versailles Arabidopsis natural variants. 51748 records from Museu Paraense Emilio Goeldi - Ictiology Collection. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 91 records from European bison in Białowieża Primary Forest. 800 records from PSUZC-Amphibians Collection. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 29 records from Potential indicator species of climate changes occurring in Québec, Part 1: the small brown lacewing fly Micromus posticus (Walker) (Neuroptera: Hemerobiidae). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 40530 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 7756 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 1 records from Protozoa ZMK. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 3 records from Collection Crustacea - ZSRO. 11762 records from Chrysomelidae of the Carpathians. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 882456 records from South Australia Fauna Observations. 15956 records from Algae (S). 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 10255 records from Araneae Collection. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 14602 records from Fungus herbarium, UiB. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 2920 records from HSU Wildlife Mammals. 146809 records from OHN. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 303 records from Ichthyologie ZMK. 51 records from Packer Collection / Xenochilicola bees, Chile. 2 records from Amphibia ZMK. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 119 records from Various insect orders, NEF. 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 1 records from On the Chilopoda from Turkey. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 1129 records from Upper Silesian Museum, Insect Collection. 37820 records from Belgian Coccinellidae - Ladybird beetles in Belgium (INBO subset). 1 records from Oribates angulatus. 1626 records from Ornithologie ZMK. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 2 records from Cnidaria ZMK. 6622 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 3387 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 3 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 906 records from Digital Florula - Las Cruces Biological Station. 2172 records from Coleccin de Reptiles. 24121 records from Endemic plants of the Congo basin. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 1 records from Celaeno spinosa. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" 1989-1996. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 30 records from Specimens from India at the University Museum at the University of Bergen. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 2913345 records from Especímenes INBio. 632 records from MVZ Hildebrand Collection (Arctos). 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Oribates badius. 1 records from Nothrus bicarinatus. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 52 records from The high alpine bee fauna (Hymenoptera: Apoidea) of the Zillertal Alps, Austria. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 158552 records from Lund Museum of Zoology (MZLU). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 12876 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 2 records from Vermes ZMK. 1 records from Ctenophora ZMK. 382 records from Reptilia ZMK. 39 records from Arachnologie ZMK. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 1 records from Bryozoa ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 27290 records from Bird Monitoring Data. 103 records from Mammalogie ZMK. 32109 records from Herbier de Nouvelle-Calédonie. 155255 records from CAS Invertebrate Zoology (IZ). 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 576881 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Nothrus bispinosus. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3221 records from Road Kill Survey. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 26 records from Schwedische Oribatei (Acari). III.. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 5199 records from FCAB - Herbário Friburguense. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 1 records from Tunicata ZMK. 400 records from Colección Hidrobiológica del Chocó. 1 records from Porifera ZMK. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 16621 records from Crustacea collection of National Museum of Nature and Science. 10840 records from Bird skin collection, Natural History Museum, University of Oslo. 6 records from Echinodermata ZMK. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 1243 records from Crustacea ZMK. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 2 records from Pantopoda SMF. 17 records from Malakologie ZMK. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1 records from On centipedes (Chilopoda) of Albania, 2. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 4 records from New country records of reptiles from Laos. 89 records from Collection Crustacea - PUM. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 83679 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 1 records from Nothrus convexus. 200 records from Zoological collection of the National Museum. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 749213 records from Historical Bird Atlas. 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 564 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 5155977 records from Australia's Virtual Herbarium. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 1029 records from Freshwater plants of Cameroon. 1 records from On the Chilopoda from Turkey. 61 records from Shrews of Poland. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 11251 records from Herbarium areqvipense (HUSA). 1641 records from NCSM PaleoBotany Collection. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 30926 records from Annelida collection of National Museum of Nature and Science. 1 records from Die Chilopodenfauna Griechenlands. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 9056 records from Tunicates collection (IT) of the Muséum national d'Histoire naturelle (MNHN - Paris). 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 5 records from New records of Paraleptophlebia werneri Ulmer, 1920 and P. strandii (Eaton, 1901) from Finland (Ephemeroptera, Leptophlebiidae). 257 records from Seewasen. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 30 records from Guadeloupe_Taro. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 1 records from Oribates orbicularis. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 1658 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 2080 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 9 records from Chenopodium vulvaria. 631 records from UCM Bird Eggs/Nests Collection (Arctos). 21091 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1415 records from Plant observations from Białowieża National Park. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 54233 records from Naturalis Biodiversity Center (NL) - Mammalia. 3045 records from ESAS cetacean sightings from 1980 to 2003.. 9 records from A new species of Margaromantis Piza, 1982 (Insecta: Mantodea) from Brazil. 1993964 records from Museum of Comparative Zoology, Harvard University. 6821 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 299586 records from SEAPOP NINA. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 1614 records from Culture Collection of Algae. 28370 records from UAM Bird Collection (Arctos). 688 records from Algae, Norwegian College of Fishery Science. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 645788 records from Norwegian Biodiversity Information Centre - Other datasets. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 29532 records from MPM Herpetology. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 1 records from Arthropoden aus südostalpinen Höhlen.. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 7000 records from CCBER Ornithology Collection. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 7 records from (Table 4) New palynological record of sediments from Odderade. 21694 records from arim. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 48 records from Tardigrada collection of National Museum of Nature and Science. 3117 records from Naturalis National Natural History Museum (NL) – Coelenterata. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 38841 records from Herbier de Strasbourg. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 39 records from Colección de Urocordados. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 1 records from Nothrus palliatus. 88693 records from Ichthyology Collection - Royal Ontario Museum. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 15 records from Chenopodium. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 7551636 records from Birds Australia, Birdata. 21541 records from Herbarium of the Université Libre de Bruxelles. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 1119094 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 1 records from Flora of Suriname, volume VI, part I. 194165 records from Vascular Plant Herbarium, UiB. 12509 records from The Bat Conservation Trust - Hibernation Survey. 56302 records from Kathryn Kalmbach Herbarium. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 37558 records from Tasmanian Museum and Art Gallery provider for OZCAM. 98 records from Colección Nacional de Heliconias. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 9948 records from Bees of Canada / Gschwendtner property collection. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 6211 records from NMMNH Mammal. 1695 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 6004 records from Colección Limnológica Universidad de Antioquia. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 29087 records from Naturalis Biodiversity Center (NL) - Collembola. 1911651 records from Consortium of California Herbaria. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 8629 records from National Taiwan University. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 21752 records from HUCS - Herbário da Universidade de Caxias do Sul. 34 records from National System of Protected Areas in Poland - Fungi. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 35685 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 607 records from Líquens d'Andorra. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 798 records from Biological Records Centre - Irish Otter Dataset. 1 records from Zetes latipes. 157237 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 6 records from Mammalia (JNHM-MM). 34 records from New records in vascular plants alien to Kyrgyzstan. 163 records from Entomofauna laguna El Tinije. 97672 records from CAS Ornithology (ORN). 1 records from Zetes morticinus. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 4852611 records from Bird Ringing Centre in Sweden (NRM). 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 70111 records from Kyushu University Museum Coleoptera Collection. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 4399 records from Fundacin Miguel Lillo - Coleccin Entomolgica. 2923 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 8518 records from Upper Silesian Museum, Bird Observations. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 104520 records from Recent Invertebrates Specimens. 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 49637 records from Monitoring data from the federal state Hesse (Germany). 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 3002 records from Colección de Peces Universidad Católica de Oriente. 666165 records from iNaturalist research-grade observations. 36459 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9787 records from Finnish Entomological Database: Hymenoptera. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 18900 records from UCBG TAPIR Provider. 1 records from Hypochthonius rufulus. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 77 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria (Gastropoda). 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 1 records from Oribates ovatus. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 3015 records from Aquatic Oligochaeta of Ireland. 1 records from Hoplophora crinita. 162886 records from CONN. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 807 records from Reunion_Coffea. 2 records from Neue Milbenarten aus Kärnten. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 63961 records from observe_tuna_bycatch_ecoscope. 10866 records from Heteroptera of Ireland. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 21749 records from University of Lethbridge Herbarium (LEA). 10 records from A new species of Orthosiphon (Lamiaceae) from Angola. 1900 records from Fungi Collection. 95 records from Ortelsbruch - Hangmoor bei Morbach. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 304689 records from Aranzadi Ringing Scheme (bird ring-recovery data). 1077 records from BioGIS - Fish - HUJ collections. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 151 records from UCM Vertebrate Observations Collection (Arctos). 37664 records from H.A. Stephens Herbarium. 4 records from A new ant genus from the southwestern United States.. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 13968 records from NYSM Birds. 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 169 records from HTSAw - Xiloteca do Trópico Semiárido. 1733 records from Birds collection of Abiko City Museum of Birds. 2043 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 30000 records from Birds collection of Yamashina Institute for Ornithology. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 1808 records from Fongs d'Andorra. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 592 records from Spiders_of_French_Guiana. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 21188 records from National Bat Database of Ireland. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 4498 records from Flora of Japan Specimen Database. 182 records from Faunistic Diversity of Spiders (Araneae) in Galichitsa Mountain (FYR Macedonia). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 33173 records from Global Lacustrine Diatoms. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 4067 records from Coleção de Polychaeta do Museu Nacional. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 (Araneae, Tetragnathidae) with notes on habits and conservation status . 11 records from Pollen profile from sediment core AV14_K2-1. 4745 records from Herbier A. Le Grand (BOUM). 8780 records from HPBR - Herbário Padre Balduino Rambo. 24 records from Tauchen und Meer. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cinclidae. 1594 records from Musée Vert ornithology collection. 1 records from Murcia trimaculata. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 181 records from Alien Species in Poland - Animals. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1752 records from Herbier National de Mauritanie (HNM). 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 8706 records from NINA botanical collection. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 419514 records from Meadow and Pasture Inventory (SJV). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 10329 records from KUBI Ichthyology Tissue Collection. 110017 records from Louisiana State University Herbarium. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 353326 records from UCJEPS TAPIR Provider. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 1035 records from National Museum Of Marine Science & Technology. 55 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 387106 records from University of California Museum of Paleontology. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 31273 records from SABCA. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 4611 records from DMNS Marine Invertebrate Collection (Arctos). 84521 records from BioGIS - Vascular plants - INPA database. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 73167 records from ALCB - Herbário Alexandre Leal Costa. 4959 records from HUSC - Herbário Unisanta. 195867 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 2966 records from Bolivian Amazon lowland fish metacommunity data. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 1 records from Zur Kenntnis der Lithobiiden. 1 records from Damaeus bicostatus. 19526 records from Wildbook for Whale Sharks. 78456 records from KUBI Vertebrate Paleontology Collection. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 23 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 201581 records from CAS Ichthyology (ICH). 1 records from On the Chilopoda from Turkey. 10234 records from Collection entomologique Barthélémy. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 31 records from First description of the worker caste of Nylanderia smythiesii (Hymenoptera: Formicidae). 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 1 records from Nothrus biciliatus. 17447 records from Swedish Board of Fisheries (Fiskeriverket) - National Register of Survey testfishing. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 850 records from Shellfish (NHMK-MS). 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 1914 records from Macrophytes_CLF. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1447 records from Odonata of the Congo River 2010 expedition. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 25128 records from rmca-albertine-rift-butterflies. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 40697 records from Mammals housed at MHNG, Geneva. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 10000 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 131642 records from mel. 1 records from Nothrus piceus. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 18004 records from Census of the animals of Benin. 6 records from First record of Tettigettalna mariae (Quartau & Boulard 1995) (Insecta: Hemiptera: Cicadoidea) in Spain. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 39 records from ECOCEAN MantaMatcher. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 1166 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 84 records from BIRDRACE Bielefinken. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 613 records from Countryside Council for Wales - Shad Monitoring data. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 5459 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 6033757 records from NMNH occurrence DwC-A. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 14605 records from DMNS Mammal Collection (Arctos). 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 91 records from BIRDRACE SchrägeVögel. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 1489 records from Herbarium Rhoenmuseum Fladungen. 8441 records from Natural England - Batsites inventory for England. 428264 records from Essig Museum of Entomology. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 1266 records from Actinomycetes Collection in BCRC. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 27299 records from NCSM Vertebrate Paleontology Collection. 3327 records from BioGIS - Mammals - SPNI. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 252125 records from Moths Ireland. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 110 records from Birdrace-LiLaMai-Vechta. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 96 records from Birdrace-federleser-Herford. 92 records from Birdrace-Team_BO-bachter-Bochum. 85 records from Birdrace-Die_Paradiesvögel-Herford. 72 records from Birdrace-Buteo2DO-Dortmund. 162 records from Siegen/ Gymnasium Am Löhrtor. 83 records from Spechtwald. 100 records from Grenzturm Hohen Neuendorf. 52 records from Fledermaus. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 128 records from Birdrace-Brut-Wetteraukreis. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 114 records from Birdrace-Finkenspötter-München. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 112 records from Birdrace_Die_Borner-Viersen. 111 records from Birdrace-Uhulogen-Lippe. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 108 records from Birdrace-TriumVIErat-Viersen. 105 records from Birdrace-ARKONAuten-Rügen. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 95 records from Birdrace-Buteo1_DO-Dortmund. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 91 records from Birdrace-Enger_am_Spektiv-Herford. 127 records from Birdrace_Schräge_Vögel-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 25883 records from Monitoring data from the federal state Saxony (Germany). 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 28 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 57495 records from TNHC Ichthyology Collection. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 2 records from Filling in the gap: two new records and an updated distribution map for the Gulf Sand gecko Pseudoceramodactylus khobarensis Haas, 1957. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 109 records from Birdrace-Team_Charadrius-Günzburg. 100 records from Birdrace-Meister_der_Herzen-Kleve. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 34 records from Borkhart. 342 records from Kremmer Luch. 271 records from Beweidungsprojekt an der Nesse. 80 records from Förderzentrum Schmölln. 122 records from Kloster Eberbach. 97 records from LauWi. 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 120 records from Birdrace-Kosmos_Racer-Freising. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 2413 records from Literature based species occurrence data of birds of North-East India. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 101 records from Birdrace-Herford-Birder-Herford. 103 records from Birdrace-Die_Nachtigallen-Herford. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 76 records from Birdrace-Birding_for_Nature-Bonn. 59 records from Im Bauerngarten. 2818 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 360 records from Küstenschutzwald. 100 records from Feriendorf Ober-Seemen. 144 records from Ehmkendorf. 151 records from Isarufer. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 37 records from Berlin - Treptower Park / Karpfenteich. 69 records from Lassentiner Moor (Niepars). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 97 records from Döchtbühlwald (Bad Waldsee). 233 records from Föhrenried (Fronreute und Baindt). 20 records from Motzener Tonsee. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 39 records from Südpark (Bochum-Wattenscheid). 325 records from Triebesbach (Zeulenroda-Triebes). 54 records from Wiese am Unterbecken. 219 records from Umgebung der Grundschule Oderberg. 101 records from Naturhausgarten. 149 records from Wirbach. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 180 records from Paul-Gerhardt-Schule Dassel. 1 records from Oribates mollicomus. 145 records from privater Garten. 54 records from Ludwigshofen. 71 records from Bolzplatz. 117 records from Wassermann. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 198 records from FNL e.V.. 114 records from Flora. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 70 records from Lech 2001. 55 records from Waldsee. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 113 records from Hochschulgelände (Bremen). 57 records from Heidesee / Halle. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 5036 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 44 records from "Schlechteberg" Ebersbach/Sa.. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 101 records from Naturgrundstück (Eutin). 245 records from Kiesgruben Wemb. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 69 records from Schulgarten mit Klasse 8a (Essen). 84 records from Roter Berg Werdau (Leubnitz). 57 records from Waldhusener Moor (Lübeck-Kücknitz). 15 records from AKG-Bensheim. 263 records from Artenvielfalt Kreis Gießen. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 270 records from Regenrückhaltebecken (Zeulenroda). 282 records from Deponie Klausdorf. 23 records from Alter Nördlicher Friedhof (München). 313 records from Stadtpark Herzberg (Elster). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 167 records from Zielbach (Töll). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 45 records from Flusswerder in der Weser (Hameln). 56 records from Zitadelle Berlin-Spandau (7b). 64 records from Kabelskebach (Kabelsketal, Saalkreis). 150 records from Steinbruch Mainz-Weisenau. 22 records from Dellwiger Bach (Dortmund). 69 records from "Schwarzes Teich" (Waldpark Radebeul). 10 records from Kita-Wäldchen Fuchsturmweg Jena. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 170 records from Bodenseeufer Radolfzell. 36115 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 41 records from Örtzemündung (Stedden). 96 records from Die Wuhle. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 65842 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 161 records from Schussenaue bei Berg. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 107 records from Landschaftsschutzgebiet Buchhorst 3. 18 records from Spielwiese. 9 records from Willersalpe. 54 records from Zentralfriedhof (Wien). 73 records from Varnhalt. 108 records from Mainufer. 163 records from Brander Wald (Stolberg). 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 99 records from Düne am Ulvenberg (Darmstadt). 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 103 records from Schwanseepark (87645 Schwangau). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 61 records from Artenvielfalt auf der Wiese. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 46 records from Hainbachtal in Oelsnitz/V.. 308 records from Wangerooge. 85 records from Insektenvielfalt Ahe/Weichelsee. 106 records from Schulgarten Hans-Carossa-Oberschule. 122 records from Stever. 12 records from Kindergarten. 79 records from GymnQuerfurt. 63 records from Erft in Selikum (Neuss). 59 records from Rund ums Ökohaus (Würzburg). 124 records from Wiesenbiotop am Wasserturm. 181 records from Spießwoogtal / Königsbruch (Fischbach). 103 records from Wasserwerkspark (Chemnitz). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 111 records from Ökologischer Weinberg (Guntersblum). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 4 records from Arthropoden aus südostalpinen Höhlen.. 5 records from Streuobstwiese (Mittelgasse 4). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 110 records from Obstwiese Osterberg. 98 records from Warnowtal (Rostock). 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 40 records from Flächennaturdenkmal Grubditz. 245 records from Gieselbachtal Fulda-Harmerz. 43 records from Saalewiesen Naumburg. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 43 records from Schulgelände Thurmair-Gymnasium. 244 records from WildesMoor bei Schwabstedt. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 92 records from Birkenloh. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 61 records from GE-Brühl. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 193 records from Gelände des Schulzentrums am Himmelsbarg. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 86 records from Alter Kreidebruch Saßnitz/Rügen. 113 records from Rund um das LUGY. 31 records from Nationalpark Harz Schul-AG Braunlage. 50 records from Junge Heide, Radebeul/Dresden. 18 records from Mittelstreifen. 28 records from Sandgrube Zaisertshofen. 48 records from Trockenrasen bei Dörndorf. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 35 records from Urwald 3 (Bad Waldsee). 77 records from Trockenrasen Franzigmark (Halle/Saale). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 65 records from Mauernacker (Wettsaasen). 17 records from Schutzgebiet Ochtersum. 22 records from Heilpflanzen im Hainbachtal. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 99 records from Dorfrand Mauderode. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 50 records from Artensuche auf den Elbwiesen in Radebeul. 59 records from Oschenberg, NO von Bayreuth-Laineck. 4 records from Schulbiotop und Brigach (Villingen). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 153 records from Selztal bei Friesenheim. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 28 records from Uferzone Wipper (Biesenrode). 22 records from Breitkopfbecken (Berlin-Reinickendorf). 62 records from Amtsrain Apolda-Zottelstedt. 28 records from Hainbachtal bei Oelsnitz / V.. 60 records from Schafsweide Seniorenhaus Berghof. 214 records from Binsenwiesen. 155 records from Bammentaler Duft- und Heilkräutergarten. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 147 records from NABU-Auerochsenweide. 172 records from Dalbekschlucht. 93 records from Höltigbaum. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 107 records from vegoek. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 32 records from Schulhof Sandhofenschule (Mannheim). 79 records from Balkon (Norderstedt). 212 records from Artenvielfalt im Beckerbruch (Dessau). 160 records from Wirbach-Taubental (Bad Blankenburg). 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 19 records from Goethe-Hauptschule/Projekt I-10. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 139 records from NSG Leist bei Ziegenhain. 95 records from Vielfalt verschiedener Wiesen. 53 records from Weidegut Rechab. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 94 records from Kochertgraben II. 47 records from Neanderthal. 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 207 records from Biosphäre Bliesgau. 54 records from Weidegebiete in der Selzrenaturierung. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 79 records from Birdrace-Bielefinken-Bielefeld. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 102 records from Industriebrache (Kempen). 46 records from 8c. 21 records from Bach. 221 records from Römertal (Steinpleis). 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 29 records from Naturerfahrung. 87 records from Klütwald. 40 records from Schulhof Liebfrauenschule Oldenburg. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 49 records from Dörnberg. 55 records from Flora und Fauna am Mittelrheintal. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 101 records from Isartal Dingolfing. 58 records from Weidewirtschaft. 881 records from Moluscos Marinhos de Augusto Nobre. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 63 records from Hochschule Zittau/Görlitz. 98 records from Rund ums Cani. 15 records from Regenwasserabfangsbecken (Erlenbach). 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 60 records from NABUGEO1. 10 records from Feuchtwiesen Wippertal bei Wippra. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 172 records from Leben im Finkensteiner Moor. 97 records from Landschaftspark St.Leonhard-Deisendorf. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 100 records from Birdrace-The_Ringers-Friesland. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 23 records from Wiese Niederaula. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 62 records from Zoo Frankfurt. 36 records from Selz (Ingelheim am Rhein). 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 142 records from Kinderbauernhof Pinke-Panke. 48 records from Morphologische Daten von Natrix. 71 records from Birdrace-do_elster_Dortmund. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 81 records from Stadtpark Schmölln. 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 36 records from Plöwener Wald. 31 records from Regenwasserabfangbecken. 117 records from Naturschutzgebiet Kochertgraben. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 35 records from Gym Freyung. 86 records from Naturerlebnisraum Koppelsberg (Plön). 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 69 records from Entdeckertour am Muldestausee 1/05. 40 records from Öhmdwiesen und Göldern (Konstanz). 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 128 records from Birdrace_turbine_untersee-Konstanz. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 39 records from Soolbach-Tal. 122 records from Birdrace-Hügelland-Mainz/Bingen. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 42 records from sbosch. 89 records from Birdrace-Team_Wangerooge-Friesland. 53 records from Bad Bodenteicher Heide. 13 records from Garten Hamburg Uhlenhorst. 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 57 records from Schulgarten Fichteschule. 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 39 records from Stausee Weiditz. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 44769 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 63 records from Sternwiese Mülheim-Broich. 81 records from Birdrace-Die_Ornithomaten-Herford. 51 records from Steinbachtal (Würzburg). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 47 records from Schulgelände Ceciliengymnasium. 21 records from Tauchen und Meer 02. 51 records from Mühlenbach bei Buxtehude. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 64 records from Issumer Fleuth. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 134 records from Birdrace-Team_Havelland-Havelland. 155 records from Birdrace-Usedommeln-Ostvorpommern. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 133 records from Wulfsmuehle/Pinnau. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 31 records from Kurler Busch (Scharnhorst). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 65 records from LSG "Großes Bruch". 21 records from Riedkanal Bötzingen. 78 records from Birdrace-Die_Laufenten-Braunschweig. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 54 records from Park Schönfeld (Kassel). 57 records from Garten in Schmölln. 51 records from Schrebergarten Düsseldorf Oberkassel. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 4472 records from MVZ Bird Observations (Arctos). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 39 records from Regenrückhaltebecken Bad Bevensen. 10 records from Ökowerk Emden. 15 records from Die geheimnisvolle Welt der Spinnen. 84 records from Streuobstwiese Haus Zeitz. 26 records from Erhard Sopp. 27 records from Vögel. 13 records from Tiere im Teichgebiet. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 11 records from Waldgebiet Todtnau- Sonnhalde. 81 records from Schulgarten-St.-Georg-Gymnasium. 26 records from Schulteich Heinrich-Mann-Schule. 27 records from Zwickau- Schwanenteich. 1 records from Hoplophora ardua. 15 records from Beisetal bei Niederbeisheim. 709 records from Upper Silesian Museum, Bird Collection. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 29 records from Insekten. 3 records from FFR Hausen. 9 records from Wiesendreieck Luckenwalde. 17 records from Tierpark Zittau. 64 records from Schafheide im Böblinger Wald. 64 records from Pilzlehrwald. 101 records from Hoher Stein Kallenhardt. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 23 records from AKG-Gelände in Bensheim. 24 records from Kaisertal. 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 22 records from Kaltenkirchen Brache. 12 records from Kinderwald Hannover. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 5 records from Feuchtwiese. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 11 records from Privatteich(St.Leon). 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 4 records from Sächsische Schweiz (Wehlener Gebiet). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 8 records from Eichendorf Weiher Schwalbach a.Ts.. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 5 records from Schulinnenhöfe (Gelsenkirchen). 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 371 records from Bannwald Burghauser Forst. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 369 records from BIRDRACE Havelland. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 274 records from BIRDRACE Asiola-Quartett. 157 records from BIRDRACE Rheinische Wasserrallen. 82 records from BIRDRACE Buteo2DO. 95 records from BIRDRACE accipiter hardcore birding. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 102 records from BIRDRACE Buteo1DO. 103 records from BIRDRACE Die Otzberger. 174 records from BIRDRACE Bon(n)apartemöwen. 132 records from BIRDRACE Die Wetterauer. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 22 records from Bachabschnitt der Nette (Osnabrück). 141 records from Draubiotop Lavamünd. 57 records from Mauervegetation,Flechten und anderes. 56 records from Estetal (Buxtehude). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1174 records from Sudeniederung (Amt Neuhaus). 29 records from Brenz (Heidenheim). 23 records from Ackerrain Plönhagen. 36 records from Olympiapark (München). 20 records from Lerchenauer Baggersee (München). 28 records from Stadtpark Prinzengarten (Sigmaringen). 48 records from Heider Bergsee (Brühl). 10 records from schlittschuhweiher. 20 records from Mikroorganismen. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 36 records from Salzwiese Diekskiel. 6 records from Fließgewässeruntersuchung am Haselbach. 13 records from Warnowufer Groß Klein. 21 records from LBV-Kindergruppen Markt Tussenhausen. 15 records from Kirchheller Heide ( Bottrop). 10 records from Bachpatenschaft Beeke. 12 records from Ohemoor (Hamburg/Norderstedt). 15 records from Urwald 2 (Bad Waldsee). 94 records from Landschaftsschutzgebiet Buchhorst 4. 59 records from Schulteich Freie Waldorfschule Darmstadt. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 7 records from Stadtrandlandschaft Apolda-Nord. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 12 records from Schulgelände Erich-Kästner-Schule. 1 records from Waldtag in und um Seelingstädt. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 2 records from Hildener Heide - Spörkelnbruch (Haan). 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from Karpfenteich, Klasse 6d. 1 records from 5. Wiener Gemeindebezirk. 1 records from Fledermäuse über der Alster (Hamburg). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 91331 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 97 records from BIRDRACE NABUhu Trier!. 32 records from Nationalpark Harz Juniorranger. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 68 records from Streuobstwiese. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 19 records from Glemstal (Leonberg). 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 24 records from Ornithologische Wanderung um Tussenhausen. 80 records from Lahnufer in Villmar. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 27 records from Wiese hinter der Schule (Darmstadt). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 23 records from Tümpel Schulbiologiezentrum. 15 records from Bodentiere rund um die Schule. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 721 records from IBF Monitoring of Plant Galls. 13 records from FND "Weißer Berg" Leißling. 45 records from Georgs-Padd (Wangerooge). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 16 records from Im und um das Schulhaus. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 8 records from Krittenhorster Wald (Ostkilver). 23 records from Wattuntersuchung (Cuxhaven). 1 records from Graureiher in Lans. 34 records from Wattenmeer-Safari (Wurster Watt). 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 6 records from Sächsische Schweiz (Pfaffenstein). 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 40 records from Tiere und Pflanzen um uns herum !. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 27 records from Bäche im Mooswald (Vörstetten). 17 records from Kohlbach (Sulzfeld). 18 records from Naturtag. 15 records from Tiere. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 1 records from Haslauer Moor. 4 records from Neues Testprojekt. 6 records from Boimstorfer Sundern. 5 records from Fledermäuse u. nachtaktive Insekten. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 555 records from FFH-Gebiet "Calwer Heckengäu". 13 records from Tag der Artenvielfalt am Bruckenwasen. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 15 records from Kühnauer Aue und Kühnauer See. 74 records from Schulwald Grundschule Brügge. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 126 records from Schulwald Marksuhl. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 161 records from BIRDRACE Nord-Seh-Team. 145 records from BIRDRACE Dith Marsh Sandpiper. 279 records from BIRDRACE Wannacks Topti(c)ker. 138 records from BIRDRACE Arkonauten. 258 records from BIRDRACE Raumpatrouille Oriolus. 1 records from Murcia ephippiata. 65 records from BIRDRACE Federal Birds of Investigation FBI. 69 records from BIRDRACE Pfeifenten. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 80 records from BIRDRACE Falkenberger Fluppis. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 135 records from Waldi-Weiher. 3 records from Blankenfelder See. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 52 records from Naturschutzstation Weinberghaus (Dessau). 169 records from Expedition "Schulgelände". 517 records from Schulzentrum "Parc Hosingen". 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 274 records from Bernhardsthal. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 278 records from BIRDRACE Usedommeln. 144 records from BIRDRACE Die Mohrenlerchen. 287 records from BIRDRACE Pody und Co. 139 records from BIRDRACE Turbine Untersee. 254 records from BIRDRACE Thüringer Becken-Birders. 140 records from BIRDRACE Guckers Offenbach. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 91 records from BIRDRACE NABU LV Hessen. 95 records from BIRDRACE BiBi. 98 records from BIRDRACE Die Paradiesvögel. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 126 records from BIRDRACE Duckehühnchen. 112 records from BIRDRACE Gütersloher Gimpel. 44 records from Wiesen am Treffpunkt Freizeit. 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 101 records from Steinbruch Kronungen. 85 records from Rund um den Hainbergsee. 214 records from Pflanzen und Tiere im Burgwald. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 114 records from BIRDRACE LiLaLau. 18 records from Landschaftsschutzgebiet Buchhorst2. 47 records from Schulgelände Grolland. 69 records from BIRDRACE Mathilden-Käuze. 84 records from BIRDRACE Vogelscheuchen. 1499 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 89 records from Schulgelände Paul-Gerhardt-Schule. 80 records from Landschaftsschutzgebiet Schmutterwald. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 61 records from Fürstenberger Ralley Teil 3. 107 records from Müritz-Nationalpark. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 359 records from Pöhlberg bei Annaberg. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 1314 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 93 records from Haarbach Höfe. 146 records from LK 11 im Mönchspark. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 366 records from Weinberg Reichersdorf. 313 records from BIRDRACE Gätkes Erben. 269 records from BIRDRACE Kosmos-Racer. 272 records from BIRDRACE Niederlausitz-Team. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 256 records from BIRDRACE Upupa epöpse. 118 records from BIRDRACE Die Lippegeier. 78 records from BIRDRACE leucorhö statt logorrhö. 82 records from BIRDRACE Die Ziegeneier. 84 records from BIRDRACE Avinauten. 166 records from BIRDRACE Die Düsselmöwen. 96 records from BIRDRACE OAG Neuwerk. 96 records from BIRDRACE Emslandracer. 101 records from BIRDRACE Enger am Spektiv. 102 records from BIRDRACE Westfälische Nachtigallen. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 103 records from BIRDRACE federleser. 104 records from BIRDRACE Erlanger Piepmätzchen. 79186 records from All Ireland Non-Marine Molluscan Database. 105 records from BIRDRACE Kiesmätze. 105 records from BIRDRACE coesfelder_vogelkundler. 106 records from BIRDRACE Ave Goettingen!. 134 records from BIRDRACE Griffin Wood Warblers. 131 records from BIRDRACE Brut. 99 records from BIRDRACE TEAM BO-BACHTER. 100 records from BIRDRACE Stuttgart 100 trööt. 102 records from BIRDRACE Willi goes Birding. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 115 records from BIRDRACE Die UHULOGEN. 111 records from BIRDRACE Die Wendehälse. 110 records from BIRDRACE Angeliter Ornis. 121 records from BIRDRACE Immerwiederhopf. 108 records from BIRDRACE Diesmal sehen wir mehr. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 67 records from Tongrube bei Hettstedt. 173 records from FFH-Gebiet Klosterwasser/Burkau. 145 records from Gronau - auf der Suche nach dem Neunauge. 37 records from Liether Park 2 (LMS), Klasse 6c. 504 records from Schatzinsel Wangerooge. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 62 records from Hettstadt Gehäge. 113 records from Tornoer Teich. 54 records from Biotope im Schulumfeld. 116 records from Sürther Aue. 132 records from Aachtobel. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 66 records from Von der Nutzung zur Natur. 36 records from Liether Park 1 (LMS), Klasse 5b. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 79 records from BIRDRACE Blinde Hühner. 84 records from BIRDRACE Birding for Nature. 88 records from BIRDRACE Kingfisher. 90 records from BIRDRACE TicTacToe. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 176 records from BIRDRACE Professorenteam. 120 records from BIRDRACE Ornis im Einsatz. 396 records from Colección de Entomología - Auchenorrhyncha. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 17 records from Bachrenaturierung Littfe. 48 records from Wahner Heide LK 12 Biologie. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 119 records from BIRDRACE Tick, Trick und Track. 114 records from BIRDRACE Di-Bi-Di-Birder. 114 records from BIRDRACE VIE will rock you!. 112 records from BIRDRACE Hügelland zu Fuß. 109 records from BIRDRACE Die Borner. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 107 records from BIRDRACE Herford Birders. 107 records from BIRDRACE Borussia Zippammer. 2910 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 66 records from Langes Tannen(LMS), Klasse 5d. 144 records from Lustbach-Umland. 121 records from Owere Fiddel. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 54 records from VFD-H: MIttelgebirgsweide. 114 records from Liether Kalkgrube. 62 records from Lebensraum Dorf. 248 records from Schulgarten der Volksschule. 194 records from Bodenteicher Seewiesen. 61 records from Wälder im Hainbachtal. 85 records from Ober-Olmer Wald. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 54 records from Wir erkunden die Hofau, Klasse 5c. 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 269 records from BIRDRACE Dithmarscher Deichhühner. 76 records from BIRDRACE Nachtigallen. 143 records from BIRDRACE Die Laufenten. 177 records from BIRDRACE Mehr Seh Team. 102 records from BIRDRACE Niederrheinische Bartgeier. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 104 records from BIRDRACE Andechser Stativträger. 27 records from Schulgarten Waldorfschule Hassfurt. 69 records from Unter hellen Zinnen und finsteren Grotten. 57 records from Schulgarten Janusz-Korczak-Realschule. 75 records from BIRDRACE Die Kartoffelsäcke. 88 records from BIRDRACE Vogelkucker. 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 149 records from BIRDRACE Birding Bentheim. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 120 records from BIRDRACE The early birds. 402 records from Tag der Artenvielfalt in Heidelberg. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 99 records from Streuobstwiese Stedar. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 80 records from Feldweg Waldkirchen. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 17 records from Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae).. 96 records from "Ahrschleife bei Altenahr". 29 records from Waldwiese. 49 records from VFD-H.: Rheingau: Bärstadt. 269 records from BIRDRACE speedbirder. 61 records from BIRDRACE Baumläufer. 83 records from BIRDRACE Die Frankenpfeifer. 126 records from BIRDRACE Die Schwenker-Birder. 101 records from BIRDRACE nabu-rhein-main.de. 45 records from IBF Monitoring of Orthoptera. 110 records from BIRDRACE Linumer Luchschleicher. 128 records from BIRDRACE Die TUErteltauben. 94 records from FFH-Gebiet Paartal. 30 records from Geführte Wanderung im Eselsbachtal. 16324 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 31 records from Düpenauwiesen. 52 records from Aktion der Klasse H2 in Simmelsberg. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 152 records from BIRDRACE NAJU-Aspach. 40 records from BUND Naturschutzzentrum St. Julian. 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 99 records from VFD HH/SH "Pferdeweide Lemsahl". 45 records from Reusaer Wald. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 12 records from Art´n Vielfalt im Kinderwald. 58 records from Schulgarten Zinnowwald-GS. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 7 records from Die Bachspezies. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 17 records from Nachtinsekten am Muldenufer. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 30 records from Höhle am Neuweg / Sächsische Schweiz. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 77 records from VFD-RP: Taunus: Mähweide Dehe. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 6325 records from Colección Entomológica de la Universidad de Antioquia. 53 records from BIRDRACE Taubenhaucher. 33 records from Schüler erforschen die Helme-Aue. 5374 records from NX - Herbário NX. 146 records from BIRDRACE VdW Wilder Westen. 30 records from Leben auf einer Sturmfläche. 38 records from Was lebt in der Brutzwiese?. 18 records from Schulgarten der Gesamtschule Am Heidberg. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 30 records from Riekdahler Wiesen. 51 records from Kindervilla Außengelände. 1 records from Streuobstwiese Alt Necheln. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 61 records from (Table 1) Sedimentology of core D11957P. 5477 records from Colección de mamíferos de la Universidad del Valle. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 75 records from Naturpark Kottenforst-Ville 19.6.09. 63 records from Rosarium (LMS), Klasse 6a. 12 records from Flora und Fauna am Mühlberg. 192 records from "Schwarzwassertal" bei Pobershau. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 31 records from Benthic foraminifera counts of sediment core PS2644-2. 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 31 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 63 records from Rund um die Sausenburg. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 4960 records from NRM-Herpetology. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 46 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 85 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 1 records from Wildnis Sturmschaden. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 41 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 545 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fractio
Keywords: GBIF; biodiversity; species occurrences